2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16797
|View full text |Cite
|
Sign up to set email alerts
|

Technological Literacy: Design And Testing An Instrument To Measure Eighth Grade Achievement In The Technology Education

Abstract: This study was focused on the design and testing of an assessment instrument to measure eighth-grade student achievement in the study of technology. Through classroom experiences and refinement of instructional methods by trial and error, technology educators have witnessed some success (academic improvement) using hands-on, lab-based design and problem-solving instruction, but these advances have not been documented. In the year 2000, the International Technology Education Association (ITEA) introduced Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It has also been demonstrated that this teacher is successful in helping her students acquire new or improve existing skills in technology, critical thinking, collaboration, presentation and self-learning. In the research conducted by Castillo [12], it was aimed to determine the technology literacy of the students who took and did not take technology courses, and it was concluded that a module programme based on technology literacy standards increased the technology literacy levels of students. Rock and Passe [13], on the other hand, conducted a study to reveal the level of application of technology-supported education applications on social studies education at the university level.…”
Section: Related Researchmentioning
confidence: 99%
“…It has also been demonstrated that this teacher is successful in helping her students acquire new or improve existing skills in technology, critical thinking, collaboration, presentation and self-learning. In the research conducted by Castillo [12], it was aimed to determine the technology literacy of the students who took and did not take technology courses, and it was concluded that a module programme based on technology literacy standards increased the technology literacy levels of students. Rock and Passe [13], on the other hand, conducted a study to reveal the level of application of technology-supported education applications on social studies education at the university level.…”
Section: Related Researchmentioning
confidence: 99%